2019
DOI: 10.1139/cjz-2017-0328
|View full text |Cite
|
Sign up to set email alerts
|

Body size, not age, predicts parasite load in Clark’s Spiny Lizards (Sceloporus clarkii)

Abstract: Determining the factors that influence parasite load is a fundamental goal of parasitology. Body size often influences parasite load in reptiles, but it is unclear whether higher levels of parasitism are a result of greater surface area of individuals (a function of size) or of longer periods of exposure to parasites (a function of age). Using skeletochronology in a wild population of Clark’s Spiny Lizards (Sceloporus clarkii Baird and Girard, 1852), we tested the hypotheses that (i) larger individuals have hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Olsson and Shine, 1996 ). However, Watkins and Blouin-Demers ( 2019 ) found that body size, but not age indirectly estimated by skeletochronology, predicted mite load in Sceloporus clarkii . In our study, A. erythrurus was infected by blood parasites only in individuals with an estimated age older than 300 days.…”
Section: Discussionmentioning
confidence: 99%
“…Olsson and Shine, 1996 ). However, Watkins and Blouin-Demers ( 2019 ) found that body size, but not age indirectly estimated by skeletochronology, predicted mite load in Sceloporus clarkii . In our study, A. erythrurus was infected by blood parasites only in individuals with an estimated age older than 300 days.…”
Section: Discussionmentioning
confidence: 99%
“…This association between parasite load and body size is consistent with previous observations in lizards (Schall, 1996; Garrido & Pérez‐Mellado, 2013; Halliday et al ., 2014) and fish (Lo, Morand & Galzin, 1998). Larger hosts may harbour more parasites because they have more surface area for attachment or entry, are easier to detect by parasites and their vectors, or because larger hosts are older and have had a longer time to accumulate parasites (Ruby & Dunham, 1984; Lo et al ., 1998; Blackenhorn, 2000; Watkins & Blouin‐Demers, 2019). Considering that blood‐feeding mite larvae and haemoparasitic Plasmodium infection did not decrease survival rates or growth rates of ornate tree lizard hosts, we posit that likely mechanisms are that older and larger hosts have more time to accumulate a higher parasite load, are easier to detect by parasites, or provide more space for attachment.…”
Section: Discussionmentioning
confidence: 99%
“…We fixed slides in methanol for one minute and then stained them with Wright–Gemsia stain. To assess Plasmodium infection load, we examined 5000 red blood cells under a light microscope at 400x magnification and counted the number of infected red blood cells (Halliday et al ., 2014; Watkins & Blouin‐Demers, 2019). We used the number of infected red blood cells (per 5000 cells) as an index of Plasmodium parasite load.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller organisms in warmed environments should not only have altered rates of metabolism, growth, and reproduction, but also experience changes in the number/abundance of predators or parasites exploiting them, as expected from the size spectra for predation and parasitism documented in this review (see Section 3). Such spectra may even apply within species (see e.g., [155,[294][295][296][297][298][299]) and thus may be pertinent for intraspecific changes in body size caused by temperature changes. Furthermore, temperaturecaused shifts in body size may change prey/host preferences by size-selective predators, herbivores, and parasites [60-64, 200, 214, 215, 300-303].…”
Section: Practical Applications Of Size Spectra For Species Interactionsmentioning
confidence: 99%